Use of Synthetic Osteochondral Implants to Treat Bilateral Shoulder Osteochondritis Dissecans in a Dog - Danielski, Alan; Farrell, Michael (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Case Description An 8-month-old American Bulldog was presented for assessment of bilateral thoracic limb lameness. Computed tomographic imaging revealed large, deep osteochondritis dissecans lesions in both humeral heads.Treatment and Outcome The osteochondritis dissecans lesions were debrided and the exposed subchondral defects were prepared to receive synthetic grafts. Circular implants consisting of a surface layer of polycarbonate urethane and a deep layer of lattice-type titanium were implanted into the osteochondral defects to reconstruct the articular surface topography. Follow-up clinical examination 1.5, 3 and 9months postoperatively revealed a lack of signs of shoulder pain and resolution of thoracic limb lameness. Nine-month follow-up radiographs showed radiographic evidence of osteointegration of both implants.Clinical Relevance Synthetic osteochondral implantation in the caudocentral aspect of the humeral head appeared technically feasible and effective in resolving lameness caused by humeral head osteochondritis dissecans.
Keywords: SynACART; dog; joint resurfacing; OCD; osteochondritis dissecans